2021
DOI: 10.3390/foods10050935
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Glycosylated Aroma Precursors in Vitis vinifera Fruit and Humulus lupulus Hop Cones and Their Roles in Wine and Beer Volatile Aroma Production

Abstract: Volatile aroma compounds found in grapes and hops may be present as both free volatiles and bound glycosides. Glycosides found in the raw materials are transferred to their respective fermented beverages during production where the odorless compounds may act as a reservoir of free volatiles that may be perceived by the consumer if hydrolyzed. A review of the literature on grape and wine glycosides and the emerging literature for glycosides in hops is presented in order to demonstrate the depth of history in gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 123 publications
(201 reference statements)
0
6
0
Order By: Relevance
“…Muscat aroma is closely related to the content of terpenes, the most abundant of which are monoterpenes including linalool, geraniol, nerolidol, citronellol, geranic acid, and α-terpinol [26]. Fenoll [17] et al studied the type, content, and aroma contribution of monoterpenes during the development of muscat grapes and concluded that linalool was the most important contributor to the aroma.…”
Section: Discussionmentioning
confidence: 99%
“…Muscat aroma is closely related to the content of terpenes, the most abundant of which are monoterpenes including linalool, geraniol, nerolidol, citronellol, geranic acid, and α-terpinol [26]. Fenoll [17] et al studied the type, content, and aroma contribution of monoterpenes during the development of muscat grapes and concluded that linalool was the most important contributor to the aroma.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these glycosidically bound volatile components are important potential sources of aroma compounds as strong volatiles in Okinawan pineapple for storing chavicol and eugenol with strong characteristic medicinal-herbal aromas [27,35]. This result provides important information on the potent aroma releases from pineapples of different cultivars in post-harvest treatments, such as fermentation and storage, that may initiate the hydrolysis of glycosidically bound volatile components, and thus, extend further aroma production to the processed pineapple fruits or their derived products [12,36]. On the other hand, careful consideration must be given to the usage of the released aglycones with undesirable strong odors in processed pineapple, which may alter the overall flavor quality of the final products [36].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the style of beer, terpene alcohols are the dominant terpenes due to their hydrophilic properties, especially geraniol and linalool [60]. Interactions between hops and Saccharomyces yeast during fermentation may cause changes in the number of volatile compounds produced [61]. Studies by other scientists have shown that brewer's yeast is characterized by low β-D-glucosidase activity during beer fermentation, but some strains exhibit exo-1,2-β-glucanase activity, which has the ability to hydrolyze glycosides.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that the yeasts in the presence of these waters (PTW) during the fermentation have a greater possibility of interacting [2] with the hop compounds, which could have contributed to an increase in their content in the final product. Currently, for the purpose of this study, non-Saccharomyces yeasts with β-glucosidase activity are used, which when introduced into the hopped wort, release glycosidic precursors of aromas derived from hops [61].…”
Section: Discussionmentioning
confidence: 99%